1985
DOI: 10.1128/aac.28.4.473
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of cephalosporins in normal and septicemic rabbits

Abstract: The differences in the pharmacokinetics of cefotaxime, moxalactam, and CPW 86-363, a new expandedspectrum cephalosporin, were studied in healthy rabbits and in rabbits infected intravenously with Streptococcus pneumoniae. The pharmacokinetic analysis of concentration-time courses in the sera of infected animals according to a two compartment-model evidenced a clear decrease of drug fractions in the central compartment but enhanced drug fractions in the peripheral compartment. The shift was more pronounced in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Finally, an i.v. model of sepsis was established in chinchilla rabbits to study the pharmacokinetics of cephalosporins (82).…”
Section: Rat and Rabbit Modelsmentioning
confidence: 99%
“…Finally, an i.v. model of sepsis was established in chinchilla rabbits to study the pharmacokinetics of cephalosporins (82).…”
Section: Rat and Rabbit Modelsmentioning
confidence: 99%
“…The pharmacokinetics of cefazolin was studied in rats, and a decreased total Cl was observed as well 19 . Larger volumes of distribution and a higher Cl were observed during fever in the previously mentioned studies on other cephalosporins 10,11,16 .…”
Section: Discussionmentioning
confidence: 69%
“…Lower V 1 values were found in the subgroup of patients in whom a two-compartment model best fitted to the measured serum concentrations. Although different volumes of distribution were calculated in different studies, enlargement of the volumes during fever was reported in most studies on the pharmacokinetics of beta-lactam antibiotics, aminoglycosides and trimethoprim 10,11,[16][17][18][19][20][21] . Smaller V 1 during fever was only found for sulphadimidin in dogs and tobramycin in rats 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Healthy rabbits were injected with cefotaxime 10, 15, 30, 50, 60 and 100 mg/kg body weight [Ganzinger and Haslberger 1985;Ganzinger et al 1986 a, b;Haslberger et al 1987]. Eq.3 was used to calculate the areas of the hysteresis loops (AROHYL) in individual animals and in each dosage group (four animals per group) by population pharmacokinetic analysis.…”
Section: Distribution Coefficientmentioning
confidence: 99%
“…The methods used in these experiments, such as dosage, route of application, time of sampling from serum and interstitial fluid in implanted tissue cages etc, have previously been published [Ganzinger and Haslberger 1985;Ganzinger et al 1986 a, b;Haslberger et al 1987]. Pharmacokinetic parameters were calculated using the PttARM program both for individual values and population parameters [Gomeni t984].…”
Section: Experimental Datamentioning
confidence: 99%